2020
DOI: 10.1007/s11242-020-01522-w
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Modeling Approach to Stochastically Evaluate the Impact of Pore Network Geometry, Chemistry and Topology on Fluid Transport

Abstract: Fine-grained sandstones, siltstones, and shales have become increasingly important to satisfy the ever-growing global energy demands. Of particular current interest are shale rocks, which are mudstones made up of organic and inorganic constituents of varying pore sizes. These materials exhibit high heterogeneity, low porosity, varying chemical composition and low pore connectivity. Due to the complexity and the importance of such materials, many experimental, theoretical and computational efforts have attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…As an example for another gas, Li et al reported that CO 2 solubility in water decreases within hydrophilic kaolinite nanopores while it increases within hydrophobic pores. To generalize the results as a function of pore width and pore chemistry, Apostolopoulou et al , showed that it is possible to employ a mesoscale approach based on kinetic Monte Carlo, once selected results from atomistic MD simulations are available.…”
mentioning
confidence: 99%
“…As an example for another gas, Li et al reported that CO 2 solubility in water decreases within hydrophilic kaolinite nanopores while it increases within hydrophobic pores. To generalize the results as a function of pore width and pore chemistry, Apostolopoulou et al , showed that it is possible to employ a mesoscale approach based on kinetic Monte Carlo, once selected results from atomistic MD simulations are available.…”
mentioning
confidence: 99%